Lung Recruitability Is Better Estimated According to the Berlin Definition of Acute Respiratory Distress Syndrome at Standard 5 cm H2O Rather Than Higher Positive End-Expiratory Pressure: A Retrospective Cohort Study*. Issue 4 (April 2015) - Caironi, Pietro; Carlesso, Eleonora; Cressoni, Massimo; Chiumello, Davide; Moerer, Onner; Chiurazzi, Chiara; Brioni, Matteo; Bottino, Nicola; Lazzerini, Marco; Bugedo, Guillermo; Quintel, Michael; Ranieri, V. Marco; et al.
Abstract : Objectives: The Berlin definition of acute respiratory distress syndrome has introduced three classes of severity according to PaO2 /FIO2 thresholds. The level of positive end-expiratory pressure applied may greatly affect PaO2 /FIO2, thereby masking acute respiratory distress syndrome severity, which should reflect the underlying lung injury (lung edema and recruitability). We hypothesized that the assessment of acute respiratory distress syndrome severity at standardized low positive end-expiratory pressure may improve the association between the underlying lung injury, as detected by CT, and PaO2 /FIO2 -derived severity. Design: Retrospective analysis. Setting: Four university hospitals (Italy, Germany, and Chile). Patients: One hundred forty-eight patients with acute lung injury or acute respiratory distress syndrome according to the American-European Consensus Conference criteria. Interventions: Patients underwent a three-step ventilator protocol (at clinical, 5 cm H2 O, or 15 cm H2 O positive end-expiratory pressure). Whole-lung CT scans were obtained at 5 and 45 cm H2 O airway pressure. Measurements and Main Results: Nine patients did not fulfill acute respiratory distress syndrome criteria of the novel Berlin definition. Patients were then classified according to PaO2 /FIO2 assessed at clinical, 5 cm H2 O, or 15 cm H2 O positive end-expiratory pressure. At clinical positive end-expiratory pressure (11 ± 3 cm H2 O), patients with severe acute respiratory distress syndrome had a greater lung tissue weight and recruitability than patients with mild or moderate acute respiratory distress syndrome ( p < 0.001). At 5 cm H2 O, 54% of patients with mild acute respiratory distress syndrome at clinical positive end-expiratory pressure were reclassified to either moderate or severe acute respiratory distress syndrome. In these patients, lung recruitability and clinical positive end-expiratory pressure were higher than in patients who remained in the mild subgroup ( p < 0.05). When patients were classified at 5 cm H2 O, but not at clinical or 15 cm H2 O, lung recruitability linearly increases with acute respiratory distress syndrome severity (5% [2–12%] vs 12% [7–18%] vs 23% [12–30%], respectively, p < 0.001). The potentially recruitable lung was the only CT-derived variable independently associated with ICU mortality ( p = 0.007). Conclusions: The Berlin definition of acute respiratory distress syndrome assessed at 5 cm H2 O allows a better evaluation of lung recruitability and edema than at higher positive end-expiratory pressure clinically set. Abstract : Supplemental Digital Content is available in the text.